ANALYSIS OF TECHNOLOGY ADAPTATION LEVEL AND EMPLOYEE DIGITAL COMPETENCE ON THE QUALITY OF THE FINANCIAL REPORTS (CASE STUDY: USE OF DIGITAL ACCOUNTING APPLICATIONS IN MSMES) - Wahyuni Saleh; Nur Fadhila Amri; Ahmad Jumarding (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The development of information technology requires organizations to adapt quickly to maintain the quality of financial reporting. This study aims to analyze the influence of the level of technology adaptation and employee digital competence on the quality of financial reports. The research method used is a quantitative approach with a causal research design. Data were collected through questionnaires distributed to employees directly involved in the financial report preparation process. The data analysis technique used multiple linear regression analysis to examine the effect of independent variables on the dependent variable. Validity, reliability, classical assumption tests, and the R2 coefficient were tested. The results of the study indicate that the level of technology adaptation does not significantly affect the quality of financial reports. This is because the sig. value of 0.46>0.05, technology acts as a supporting tool in the accounting process, the quality of financial reports is more influenced by professionalism and compliance with standard operating procedures. In addition, employee digital competence is proven to have a positive and significant influence on the quality of financial reports. Simultaneously, the level of technology adaptation and employee digital competence contribute significantly to improving the quality of financial reports reviewed from the aspects of relevance, reliability, timeliness, and comparability. The findings of this study indicate that improving the quality of financial reports is not only determined by the technology system used, but also by the ability of human resources to operate and utilize technology optimally.